Organizational Conflict Management Challenges (European Journal of Marketing and Economics, 2023)
There is no organization without conflict situations. It is known that 80 percent of conflict situations occur independently of human will. Its causes are people’s individual characteristics, as well as structure of the organization, conditioned by the culture established in the organization. How correctly organizational management analyzes the causes of conflicts, managing stress, diagnostic of the conflict and its management are reflected on the psychological climate of the organization. The psychological climate is directly related to the labor productivity of each member of the organization and the whole organization itself. On the background of strenuous labor relations, the potential of the organization members is spent on the settlement of the conflict environment and it takes a large part of their time budget. Proper use of time resources affects labor productivity. The Human Resources Management Laboratory which is functioning at Ivane Javakhishvili Tbilisi State University has already conducted a research in this regard. Due to the actuality of the issue, the laboratory aimed to conduct a further research about conflict situations in the organization. The research was focused on the Faculty of Economics and Business of Ivane Javakhishvili Tbilisi State University. 458 respondents were interviewed including Bachelor's and Master’s Degree Students, Professors and Administration Representatives. The questionnaire included 36 questions and 133 options of response. As a result of the research,frequency of conflict situations in the organization was established, the active link of conflict situations. The reasons for the involvement of the collective team members into the conflict have been identified. The attitude of respondents of different categories was interesting in terms of resolving conflict situations. Conflict situations combined with the rest of the stages include the analysis of the causes. Different categories of respondents differently understand the importance of analyzing the causes of conflicts. The study finally made many interesting problems clear. The results obtained were processed by the SPSS program. We have formulated the hypothesis, studied the influence of the status and the gender of a respondent (bachelor, master, professor, and representative of the administration) on up to 15 variables. Trends were revealed through the tables developed on dispersion analysis. The conclusions made on the basis of the analysis of the survey results gave us the opportunity to make recommendations for the recovering and systemic improvement of the established values in the organization. The planned events will help the collective to undergo 3 stages of self-organization, meet the needs of the members, which will improve the psychological situation in the collective. It will facilitate each member’s involvement in order to protect the organization's prestige and traditions. It is interesting to note that the majority of respondents are loyal to the university, which confirms the true fact that Ivane Javakhishvili Tbilisi State University is number one university in the country as well as in the region, is being developed and is constantly maintaining the championship and is trying to improve the conditions of the collective members.
Keywords: Conflict Management, University, Human Resources Management, Management of Higer Education Institutions